2009
DOI: 10.1158/1078-0432.ccr-08-2955
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of p53 Pathway by Nutlin-3 Induces Cell Cycle Arrest and Apoptosis in Human Rhabdomyosarcoma Cells

Abstract: Purpose: Seventy to eighty percent of rhabdomyosarcoma (RMS) tumors retain wild-type p53.The tumor suppressor p53 plays a central role in inducing cell cycle arrest or apoptosis in response to various stresses. p53 protein levels are regulated by MDM2 through ubiquitin-dependent degradation. In this study, we evaluated whether nutlin-3, a recently developed small-molecule antagonist of MDM2, has an effect on p53-dependent cell cycle arrest and apoptosis in cultured human RMS cell lines. Experimental Design: Fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 34 publications
6
82
0
Order By: Relevance
“…However, because the synergistic effects of Nutlin-3a in combination with conventional cytotoxic agents were only observed in vitro using limited dose ranges of each of these agents, detailed preclinical pharmacokinetic studies of these combinations will be required. Nutlin-3a has been shown to synergize with these drugs in other sarcoma types, with previously reported CIs similar to those reported in this study at optimal dosages (15,16). Unfortunately, these previous studies were limited to investigations of synergy at a single dose of these agents.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, because the synergistic effects of Nutlin-3a in combination with conventional cytotoxic agents were only observed in vitro using limited dose ranges of each of these agents, detailed preclinical pharmacokinetic studies of these combinations will be required. Nutlin-3a has been shown to synergize with these drugs in other sarcoma types, with previously reported CIs similar to those reported in this study at optimal dosages (15,16). Unfortunately, these previous studies were limited to investigations of synergy at a single dose of these agents.…”
Section: Discussionsupporting
confidence: 76%
“…Nutlin-3a disrupts the p53-MDM2 interaction by blocking the p53-binding pocket of MDM2, resulting in rapid stabilization of biologically active p53 protein (13). Promising results from several preclinical studies have clearly showed the therapeutic potential of Nutlin-3a in a variety of tumor types with wild-type p53, including liposarcoma (14), rhabdomyosarcoma (15), osteosarcoma (13), synovial sarcoma (16), neuroblastoma (17), retinoblastoma (18), and leukemia (19)(20)(21). In an effort to accelerate clinical implementation of p53 activators, Lane and colleagues screened a library of clinically approved drugs and successfully identified actinomycin D (ActD) as a compound that mimics the action of Nutlin-3a when administered at nongenotoxic "low doses" (22).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by several preclinical in vitro and mouse xenograft studies, which showed that Nutlin-3a can effectively activate the TP53 pathway, resulting in cell-cycle arrest or apoptosis in Ewing sarcoma (17,34), liposarcoma (7), osteosarcoma (8), rhabdomyosarcoma (35), and synovial sarcoma (36).…”
Section: Discussionmentioning
confidence: 76%
“…Real-time RT-PCR was performed using the Rotor-Gene SYBR Green PCR kit (Qiagen, Hamburg, Germany) in a Fast Real-time PCR System (Rotor Gene 6000). p53 mRNA was amplified using previously described primer pairs: 5'-AGA GTC TAT AGG CCC ACC CC -3'(forward) and 5'-GCT CGA CGC TAG GAT CTG AC-3' (reverse), and GAPDH 5'-CAT GGG GAA GGT GAA GGT CGG A-3' (forward) and 5'-TTG GCTCCC CCC TGC AAA TGA G -3' (reverse) (Miyachi et al, 2009). Relative target mRNA levels were determined using the delta-delta CT method (Schmittgen and Livak, 2008), with the formula given below (Livak and Schmittgen, 2001), and threshold value of 0.2, where the results were expressed in fold changes of treated cells compared with untreated cells.…”
Section: Methodsmentioning
confidence: 99%